Introduction and Critique of the Philosophy of Eshragh - Zohreh Saeidi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Philosophy of Eshragh is too important as it is situated between Mulla Sadra and Ibn Sina’s philosophy. Thus every book that introduces and analyzes itcan be assessed. In this book, the author, after propounding development ground of the logical – illuminated philosophy of Eshragh, focusing on biography, compilations and philosophical method. Then he debates Suhrvardi’s critique to Masha’s philosophy and afterwards indicates two realms of the ontology and epistemology in wisdom of Eshragh. Using the Suhrvardi’s compilations, especially wisdom of Eshragh, he presents philosophy of Eshragh in summary. In this essay, the author aims to introduce the book, present its summary, indicate positive and negative aspects, and suggest some points to improve it.